2010
DOI: 10.1111/j.1365-313x.2010.04389.x
|View full text |Cite
|
Sign up to set email alerts
|

Fewer genes than organelles: extremely low and variable gene copy numbers in mitochondria of somatic plant cells

Abstract: SUMMARYPlant mitochondrial genomes are split into sub-genomes, i.e. genes are distributed across various sub-genomic molecules. To investigate whether copy numbers vary between individual mitochondrial genes, we used quantitative real-time PCR in combination with flow cytometric determination of nuclear DNA quantities to determine absolute per-cell-copy numbers of four mitochondrial genes in various Arabidopsis organs and the leaves of tobacco (Nicotiana tabacum) and barley (Hordeum vulgare). The copy numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
178
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(189 citation statements)
references
References 68 publications
9
178
1
1
Order By: Relevance
“…However, since wild-type and mutant plants of the same age are being compared, any variations in nuclear or organellar DNA levels should not affect our results. It is interesting that previous studies reported a similar trend for ptDNA (Zoschke et al, 2007) and mtDNA (Preuten et al, 2010) ratios in aging cotyledons of Arabidopsis, although different samples were used in these studies (cotyledon alone versus whole seedling with roots).…”
Section: Discussion An Essential Role For the Poli Genes In Higher Plmentioning
confidence: 67%
“…However, since wild-type and mutant plants of the same age are being compared, any variations in nuclear or organellar DNA levels should not affect our results. It is interesting that previous studies reported a similar trend for ptDNA (Zoschke et al, 2007) and mtDNA (Preuten et al, 2010) ratios in aging cotyledons of Arabidopsis, although different samples were used in these studies (cotyledon alone versus whole seedling with roots).…”
Section: Discussion An Essential Role For the Poli Genes In Higher Plmentioning
confidence: 67%
“…In Arabidopsis, the number of mitochondria per cell was found to increase with cell size and over development (Preuten et al 2010). Young leaves were observed to contain approximately 300 mitochondria per cell while older mature leaves were observed to have 450 mitochondria per cell (Preuten et al 2010). Variations in mitochondrial morphology and dynamics are also evident, with the movement, fusion and Wssion of mitochondria documented (Logan 2010).…”
Section: Introductionmentioning
confidence: 91%
“…In contrast, complex II abundance was found to be the inverse, as it was high in roots and callus tissue and lower in abundance in leaves and stems (Peters et al 2012). In Arabidopsis, the number of mitochondria per cell was found to increase with cell size and over development (Preuten et al 2010). Young leaves were observed to contain approximately 300 mitochondria per cell while older mature leaves were observed to have 450 mitochondria per cell (Preuten et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…As a complication, mitochondrial DNA (mtDNA) is distributed highly heterogeneously across the individual discrete mitochondria of a plant cell that undergo frequent fusion and fission. Often, mitochondria only contain a substoichiometric amount of the full genome, and some mitochondria contain no mtDNA at all (6,170). For these mitochondria, CoRR requires additional features: upon a signal, fusion with a DNAcontaining mitochondrion needs to occur, so a change in gene expression can be achieved; alternatively, CoRR could act post-transcriptionally on mtRNA, which may be stored in mitochondria that do not contain any mtDNA.…”
Section: Figmentioning
confidence: 99%